Rapid selection of single-stranded DNA aptamers binding Staphylococcus epidermidis in platelet concentrates. (27th November 2018) - Kaur, Simran J; Gilman, Vladimir; Duong, Minh; Asher, David M; Gregori, Luisa
Staphylococcus epidermidis is the most common transfusion-associated pathogen contaminating platelet concentrates. Methods to reduce or eliminate contaminating bacteria from platelet units are critical for improving the safety of blood transfusions. We used rapid isolation of DNA aptamers (RIDA) to identify single-stranded (ss)DNA aptamers as ligands that specifically bind to S. epidermidis . Five target-specific ssDNA aptamers (76 mer) were obtained under stringent selection conditions. Aptamer SE43 demonstrated higher binding affinity compared with scrambled control. Furthermore, when binding assays were conducted in platelet concentrate, there was a twofold increase in binding affinity compared with the SE43 binding in buffer alone. Our data identified an aptamer that may be useful as a ligand to capture, detect or remove S. epidermidis contaminant from platelet concentrates.